2012
DOI: 10.1097/hjh.0b013e3283588d46
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training restores the endothelial progenitor cells number and function in hypertension

Abstract: Our data show that exercise training repairs the impairment of EPC in hypertension, which could be associated with peripheral revascularization, suggesting a mechanism for its potential therapeutic application in vascular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
56
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 44 publications
10
56
0
8
Order By: Relevance
“…Increase of the pro-apoptotic activity of Bad in SHR was confirmed, since we verified decrease of phosphorylated Bad in Ser112 and of p-Bad ser112 /Bad ratio. Moreover, our results showed that reduction of endothelial NO synthesis followed by increase in protein expression of iNOS could contribute to moderate exchange of redox homeostasis towards a pro-oxidant status, corroborating for the activation of the microvascular pro-apoptotic signaling way since the oxidative stress mediated by hypertension harms the vasodilator response and apoptosis of the endothelial cell associated with loss of microvessels 13,14,30 . Consistent to the data in the literature, ET restored the VEGF levels followed by increase in expression of VEGFR2.…”
Section: Discussionsupporting
confidence: 70%
“…Increase of the pro-apoptotic activity of Bad in SHR was confirmed, since we verified decrease of phosphorylated Bad in Ser112 and of p-Bad ser112 /Bad ratio. Moreover, our results showed that reduction of endothelial NO synthesis followed by increase in protein expression of iNOS could contribute to moderate exchange of redox homeostasis towards a pro-oxidant status, corroborating for the activation of the microvascular pro-apoptotic signaling way since the oxidative stress mediated by hypertension harms the vasodilator response and apoptosis of the endothelial cell associated with loss of microvessels 13,14,30 . Consistent to the data in the literature, ET restored the VEGF levels followed by increase in expression of VEGFR2.…”
Section: Discussionsupporting
confidence: 70%
“…Angiogenesis is a key determinant of skeletal muscle function, and previous reports in animal models and humans have shown a beneficial effect of physical exercise on factors that sustain capillarization levels in skeletal muscles (Fernandes et al 2012;Shibuya 2013). In this context, we found that the vascular endothelial growth factor A (Vegfa) was significantly increased by WR in fP8WR female mice, while no change was detected in fR1CON controls (Fig.…”
Section: Impact Of Wheel Running In the Expression Of Skeletal Musclesupporting
confidence: 55%
“…This is not entirely surprising as it has been reported that functional sympatholysis is mediated by NO in normotensive humans and animals (8,10,15,17,56). Recent evidence suggests that protein levels for endothelial NOS in the soleus muscle of SHR are significantly lower compared with WKY (18). Decreases in NOS expression could mediate reductions in the availability of NO within skeletal muscle in hypertension and may potentially account for the blunting of functional sympatholysis in hypertensive animals.…”
Section: Impairments In Functional Sympatholysis In Shrmentioning
confidence: 93%